PANIC ATTACK FIRST AID FOR PATIENTS WITH ANXIETY DISORDER - Chandra Dewi, Paramita
Panic attack is a psychological problem where a person experiences sudden extreme level of fear that lasts for up to 30 minutes. Currently, the process of handling panic attack is mostly done by doing psychotherapy (such as cognitive behavioral therapy), and medication. But both of them aren’t focused on dealing the situation when the panic suddenly occures. The research approach was carried out qualitatively by conducting literature study, triangulation data interviews (interviews with psychiatrists, panic attack sufferers, and those who had dealt with the sufferers), conducting data synthesis to produce product requirements. Through research it was found that panic attacks cause physiological changes in the body which are generally preceded by anxiety triggers. At the peak of panic, sufferers often unable to do anything or forget to do the techniques that have been taught. The ideation process began by making design alternatives, conducting online survey of 75 respondents randomly, then the design with the highest points based on parameters was chosen as the final design. Later carried on for prototyping. The final design is a wearable product consist of two devices, a smartearphone that can help remind sufferers to do grounding techniques and aromatherapy necklace that spreads lavender scent as an effective anxiety suppressor.